On the differential geometry on the non-holonomic hypersurface of the Riemannian space - Bliznikas, V. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:В. И. Близникас. Дифференциальная геометрия неголономной гиперповерхности риманова пространстваV. Bliznikas. Rymano erdvės neholonominio hiperpaviršiaus diferencialinė geometrija